2017
DOI: 10.1177/0142331217708242
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of random forest, artificial neural networks and support vector machine for intelligent diagnosis of rotating machinery

Abstract: Nowadays, the data-driven diagnosis method, exploiting pattern recognition method to diagnose the fault patterns automatically, achieves much success for rotating machinery. Some popular classification algorithms such as artificial neural networks and support vector machine have been extensively studied and tested with many application cases, while the random forest, one of the present state-of-the-art classifiers based on ensemble learning strategy, is relatively unknown in this field. In this paper, the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
136
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(136 citation statements)
references
References 42 publications
0
136
0
Order By: Relevance
“…They presented a specific taxonomy of random forest and compared the existing random forest methods. Recent research found random forest to be more robust and stable than extreme learning machines, SVM, and neural networks, especially with small training sets (Han, Jiang, Zhao, Wang, & Yin, ).…”
Section: Ensemble Methodsmentioning
confidence: 99%
“…They presented a specific taxonomy of random forest and compared the existing random forest methods. Recent research found random forest to be more robust and stable than extreme learning machines, SVM, and neural networks, especially with small training sets (Han, Jiang, Zhao, Wang, & Yin, ).…”
Section: Ensemble Methodsmentioning
confidence: 99%
“…SVM have shown excellent performance with high classification accuracies when applied to datasets with limited number of training samples [30]. Artificial Neural Networks (ANN) are mathematical models that were initially developed to mimic the complex pattern of neuron interconnections in the human brain [31,32]. Presently, a lot of feed-forward neural networks models have been extensively studied in fault detection and diagnosis of mechanical systems.…”
Section: Introductionmentioning
confidence: 99%
“…Random Forest greatly improves the robustness of the classification model by maintaining flexibility and interpretability of decision trees . Random Forest is also proven to be more efficient in dealing with imbalanced data . In this study, we also investigate the choice of other algorithms such as Gradient Boosted Trees and Support Vector Machines .…”
Section: Predictive Equivalent Mutant Classification Approachmentioning
confidence: 99%